Usage and effect of health information exchange: a systematic review - Rudin, Robert S; Motala, Aneesa; Goldzweig, Caroline L; Shekelle, Paul G (Annals of internal medicine, 2014)
Health information exchange (HIE) is increasing in the United States, and it is incentivized by government policies. To systematically review and evaluate evidence of the use and effect of HIE on clinical care. Selected databases from 1 January 2003 to 31 May 2014. English-language hypothesis-testing or quantitative studies of several types of data exchange among unaffiliated organizations for use in clinical care that addressed health outcomes, efficiency, utilization, costs, satisfaction, HIE usage, sustainability, and attitudes or barriers. Data extraction was done in duplicate. Low-quality evidence from 12 hypothesis-testing studies supports an effect of HIE use on reduced use or costs in the emergency department. Direct evidence that HIEs were used by providers was reported in 21 studies involving 13 distinct HIE organizations, 6 of which were located in New York, and generally showed usage in less than 10% of patient encounters. Findings from 17 studies of sustainability suggest that approximately one quarter of existing HIE organizations consider themselves financially stable. Findings from 38 studies about attitudes and barriers showed that providers, patients, and other stakeholders consider HIE to be valuable, but barriers include technical and workflow issues, costs, and privacy concerns. Publication bias, possible selective reporting of outcomes, and a dearth of reporting on context and implementation processes. Health information exchange use probably reduces emergency department usage and costs in some cases. Effects on other outcomes are unknown. All stakeholders claim to value HIE, but many barriers to acceptance and sustainability exist. A small portion of operational HIEs have been evaluated, and more research is needed to identify and understand success factors. U.S. Department of Veterans Affairs. (PROSPERO registration number: CRD42014007469).